2020
DOI: 10.1021/acs.jpcb.9b11702
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Influence of Size of Quaternary Ammonium Countercations on Micromorphology, Polarization, and Electroresponse of Anionic Poly(ionic liquid)s

Abstract: The size influence of quaternary ammonium countercations in poly­[4-styrenesulfonyl­(trifluoromethyl­sulfonyl)­imide]­[tetraalkyl­ammonium] (P­[STFSI]­[Nnnnn], n = 1, 2, and 3) poly­(ionic liquid)­s on dielectric polarization and the stimuli-responsive electrorheological effect is investigated by dielectric spectroscopy and rheology, and the microstructure-level understanding behind the influence is analyzed by Raman and X-ray scattering spectra. The size influence of quaternary ammonium cations is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Because the values of relative permittivity and dielectric loss of carrier liquid (silicone oil) are independent of the frequency in the measured range, the observed dielectric relaxation processes should be created from the electric polarization of suspended particles in the carrier liquid. This electric polarization may be further from either a polarization contributed by the charge relaxation inside particles or an interfacial polarization contributed by the charge's diffusion and blocking at the interface of the particle/carrier liquid owing to the two‐phase character of electrorheological suspensions ​(ERFs) [29, 30]. To clarify it, we use the Maxwell‐Wagner interfacial polarization formula to estimate the relaxation time simply according to the conductivity ( σ p ) of particles measured previously [31]: λMW=ε02εf+εpϕ(εpεf)2σf+σpϕ(σpσf) where ε 0 is the permittivity of vacuum, ε ′ p obtained by lg ε ′ ∞ = ϕ lg ε ′ p + (1‐ ϕ )lg ε ′ f is the relative permittivity of particles, ε ′ ∞ is the relative permittivity of total suspensions at high frequency, ε ′ f is the relative permittivity of the carrier liquid ( ε ′ f = 2.7), σ f is the DC conductivity of the carrier liquid, which can be negligible during calculation because it is low (∼10 −15 S/cm), and ϕ is the particle volume fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the values of relative permittivity and dielectric loss of carrier liquid (silicone oil) are independent of the frequency in the measured range, the observed dielectric relaxation processes should be created from the electric polarization of suspended particles in the carrier liquid. This electric polarization may be further from either a polarization contributed by the charge relaxation inside particles or an interfacial polarization contributed by the charge's diffusion and blocking at the interface of the particle/carrier liquid owing to the two‐phase character of electrorheological suspensions ​(ERFs) [29, 30]. To clarify it, we use the Maxwell‐Wagner interfacial polarization formula to estimate the relaxation time simply according to the conductivity ( σ p ) of particles measured previously [31]: λMW=ε02εf+εpϕ(εpεf)2σf+σpϕ(σpσf) where ε 0 is the permittivity of vacuum, ε ′ p obtained by lg ε ′ ∞ = ϕ lg ε ′ p + (1‐ ϕ )lg ε ′ f is the relative permittivity of particles, ε ′ ∞ is the relative permittivity of total suspensions at high frequency, ε ′ f is the relative permittivity of the carrier liquid ( ε ′ f = 2.7), σ f is the DC conductivity of the carrier liquid, which can be negligible during calculation because it is low (∼10 −15 S/cm), and ϕ is the particle volume fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Because the values of relative permittivity and dielectric loss of carrier liquid (silicone oil) are independent of the frequency in the measured range, the observed dielectric relaxation processes should be created from the electric polarization of suspended particles in the carrier liquid. This electric polarization may be further from either a polarization contributed by the charge relaxation inside particles or an interfacial polarization contributed by the charge's diffusion and blocking at the interface of the particle/carrier liquid owing to the two-phase character of electrorheological suspensions (ERFs) [29,30]. To clarify it, we use the Maxwell-Wagner interfacial polarization formula to estimate the relaxation time simply according to the conductivity (σ p ) of particles measured previously [31]: -5…”
Section: Conductivity and Dielectric Characteristicmentioning
confidence: 99%
“…Due to the higher ion number density in the dual-cation PILs, it exhibits higher polarizability and stronger ER response under an electric field. In addition, to study the influence of the chemical structure of the counter cation on the ER effect of anionic PILs, Zhao et al [ 50 , 92 , 126 , 130 ] synthesized poly[4-styrenesulfonyl (trifluoromethylsulfonyl) imide (P[STFSI][X]) with anionic polymer backbone and cationic counterion. It is found that the size of cations did not show a monotonic influence on the ER effect of the PILs.…”
Section: Er Responsesmentioning
confidence: 99%
“…As a new type of intelligent material, electrorheological fluid (ERF) is composed of insulating medium (such as dimethyl silicone oil) and dispersed phase particles because it can accurately affect the stress change according to the increase and withdrawal of electric field or change the strength of electric field, so as to achieve the state and characteristics we need. [1][2][3] This kind of change comes from the fact that when the different electric field strengths are applied to the ERF, the dispersed phase particles that were originally in chaotic dispersion will be instantaneously polarized due to electrostatic attraction, and the phenomenon that polarizable particles are distributed linearly in the direction of the electric field, similar to a chain structure. When the electric field is cancelled, the mutual attraction between the particles will disappear instantaneously, the polarization will also disappear at the same time, the chain structure will be destroyed, and the state of chaotic distribution will reappear.…”
Section: Introductionmentioning
confidence: 99%